Penerapan STEAM Project Based Learning “Taman Mini Imun Booster Digital Berbasis QR Code Berbantuan 4DFrame” - Eti Herawati (Jurnal Didaktika Pendidikan Dasar, 2022)
The aim of this study was to improve the learning outcomes students in the material of Cubes and Blocks by implementing the STEAM Project Based Learning "Mini Immune Booster Digital Park Based on QR Code assisted 4DFrame". This Classroom Action Research (CAR) which consists of two cycles with four meetings each, was carried out in the first semester of August 2021. The subjects of this research were class VIII 8 students consisting of 5 female students and 11 female students. The data collection technique used sheets observations, project assignments, learning achievement tests, questionnaires, interviews and photos. From the results of the questionnaire, students' attitudes towards Cube and Block learning by implementing STEAM Project Based Learning assisted 4D frame are mostly good and very good. Knowledge learning outcomes have also increased. The average score of the pre-action learning outcomes test was 69.06 with achievement B study 68.75%. In cycle 1 learning achievement increased to 75% with an average learning achievement test of 75.31 and in cycle 2 learning achievement increased again to 87.5% with an average learning achievement of 81.25. In skills competency, the average project outcome increased to 78.50 in cycle one and increased again to 87.50 in cycle two.